Wilayat al-Faqih Baina al-Fiqhiyyah wa al-Kalamiyyah - Muhammad Khalid Muslih (TSAQAFAH, 2011)
The early fourteenth century of Hijra is a new transitional phase for the historical development of Syiah Imamiyah. This can be traced by their success in establishing an Islamic state using 12 Imam Ideology which is based on “Welayat al-Faqih” system. This system is the antithesis of the theory of al-ghaibah al- kubra, which until now has been running more than 1000 years and has forbidden Shiite followers to perform various social, political and religious activities until reappearance of Imam Mahdi. As a result, many teachings of the religion cannot be applied. If this condition  continues, the Islamic teachings will be destructed in the future, so that the bearer of this idea see the necessity for the fuqaha ‘(scholars’) of Shiite who have reached the degree of “Mujtahid” to take over the role of Imam Mahdi in establishing and leading the Islamic State, thus, a guardian Jurist in a country which is built up under the system of welayat faqih, holds a supreme power, who covers the whole territory granted to the Prophet and the Imams. In spite of  saying that welayat fakih included in the category of Islamic jurisprudence, the Shiite Jurists argue that it has a dimensions of kalam, as it also discusses the problem of  “af ’âlullâh”. Eventually, the form of  the State born cannot be avoided from the format of  “Theocracy”. historical development of Syiah Imamiyah. This can be traced by their success  in establishing an Islamic state using 12 Imam Ideology which is based on  "Welayat al-Faqih" system. This system is the antithesis of the theory of  al- ghaibah al-kubra, which until now has been running more than 1000 years and  has forbidden Shiite followers to perform various social, political and religious  activities until reappearance of Imam Mahdi. As a result, many teachings of  the religion  cannot be applied. If this condition  continues, the Islamic teachings will be destructed in the future, so that the bearer of this idea see the necessity for the fuqaha '(scholars') of Shiite who have reached the degree of "Mujtahid" to take over the role of Imam Mahdi in establishing and leading the Islamic State, thus, a guardian Jurist in a country which is built up under the system of  welayat faqih, holds a supreme power, who covers the whole territory granted to the Prophet and the Imams. In spite of saying that welayat fakih included in the category of Islamic jurisprudence, the Shiite Jurists argue that it has a dimensions of kalam, as it also discusses the problem of "af'âlullâh". Eventually, the form of the State born cannot be avoided from the format of "Theocracy".